2019
DOI: 10.1111/apt.15476
|View full text |Cite
|
Sign up to set email alerts
|

Review article: direct‐acting antivirals for the treatment of HCV during pregnancy and lactation ‐ implications for maternal dosing, foetal exposure, and safety for mother and child

Abstract: Summary Background With the global efforts to eradicate hepatitis C virus (HCV), treatment during pregnancy is becoming a priority for research as this, and maternal cure should reduce vertical transmission. However, as information on the efficacy and safety of direct‐acting antivirals (DAAs) in pregnancy is generally lacking, treatment of HCV infection during pregnancy is not currently recommended. Aim To provide an overview of current knowledge regarding maternal exposure, placental handling and safety of DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 91 publications
(100 reference statements)
1
41
0
1
Order By: Relevance
“…17 , 18 In a number of dose-ranging studies analysing sofosbuvir 19 , 20 and daclatasvir 21–25 individually or in combination with ribavirin and peginterferon alfa-2a compared with placebo, no progressive dose-related adverse events were observed. A recent review on sofosbuvir-containing regimens in pregnancy 26 concluded that DAAs have a favourable safety profile in pregnancy and suggests that a 12 week DAA course could be started at the end of the second or early third trimester. The safety of sofosbuvir and daclatasvir has even been proven in patients with severely impaired renal function.…”
Section: Introductionmentioning
confidence: 99%
“…17 , 18 In a number of dose-ranging studies analysing sofosbuvir 19 , 20 and daclatasvir 21–25 individually or in combination with ribavirin and peginterferon alfa-2a compared with placebo, no progressive dose-related adverse events were observed. A recent review on sofosbuvir-containing regimens in pregnancy 26 concluded that DAAs have a favourable safety profile in pregnancy and suggests that a 12 week DAA course could be started at the end of the second or early third trimester. The safety of sofosbuvir and daclatasvir has even been proven in patients with severely impaired renal function.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, a pan-genotypic, safe, and effective DAA combination would be available to all HCV-pregnant women living with HCV diagnosed by a (cost-effective) universal screening program. 44 Hepatitis C testing should be ordered at all routine clinic visits, such as antenatal checks and well-child and vaccination appointments to ensure that those diagnosed receive appropriate treatment. Obstetricians may play a key role by implementing universal testing for HCV in pregnant women, thereby enhancing the health of mothers and identifying children at risk.…”
Section: Injection Drug Use and Mother-to-child Transmissionmentioning
confidence: 99%
“…More so, HCV infection during pregnancy is associated with an increased risk of adverse fetal outcomes such as fetal growth restriction and low birth weight [3]. Therefore, there is need to intensify efforts at PMTCT of HCV [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Awareness of the risks associated with HCV infection during pregnancy among pregnant women will create more demands for HCV screening and PMTCT interventions among them. Some authorities have argued that routine antenatal screening for HCV is not a viable option in resourceconstrained settings because the information on the e cacy and safety of antivirals for HCV in pregnancy is generally lacking, and the treatment of HCV infection during pregnancy is not currently recommended [4,5]. Nevertheless, intrauterine and peripartum transmission of HCV are both possible and higher rates are associated with a high maternal serum viral load and concomitant HIV or HBV infection, prolonged or di cult delivery, and invasive fetal monitoring during delivery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation